Dust Effect on The Performance of Optical Wireless Communication System (Journal of University of Babylon for Engineering Sciences, 2017)
In this paper wireless optical communication system (FSO) is designed through the use of software (Optisystem) . The paper also study  the effect of atmospheric dust on the performance of communication system (FSO), the effect of dust concentration on the visibility by taking a different concentrations of dust (9, 20, 40, 60, 80 100, 120) gm / month / m2 . The effect of the visibility on the attenuation of dust concentration on each of these concentrations , and calculate attenuation of dust for the  wavelengths  (784 nm, 1550 nm). The Paper also deals with effect of the transmitted laser  power on the transmitter range (propagation distance) where five different values of transmitted laser power (10mw, 20mw, 30mw, 40mw, 50mw) are taken  and the study calculates the maximum transmitter range of  each value of the transmitted power under the influence of attenuation atmospheric dust concentrations for each concentration of dust used and also for the two wavelengths (1550nm, 784nm).